The activation domain of GAL4 protein mediates cooperative promoter binding with general transcription factors in vivo. - Vashee, S (1995)
Most proteins that activate RNA polymerase II-mediated transcription in eukaryotic cells contain sequence-specific DNA-binding domains and "activation" regions. The latter bind general transcription factors and/or coactivators and are required for high-level transcription. Their function in vivo is unknown. Since several activation domains bind the TATA-binding protein (TBP), TBP-associated factors, or other general factors in vitro, one role of the activation domain may be to facilitate promoter occupancy by supporting cooperative binding of the activator and general transcription factors. Using the GAL4 system of yeast, we have tested this model in vivo. It is demonstrated that the presence of a TATA box (the TBP binding site) facilitates binding of GAL4 protein to low- and moderate-affinity sites and that the activation domain modulates these effects. These results support the cooperative binding model for activation domain function in vivo.